Screening siderophore producing bacteria as potential biological control agent for fungal rice pathogens in Thailand - Chaiharn M. (2014)
Rice (Oryza sativa) is a staple food in Thailand and, in addition, feeds around one half of the world's population. Therefore, diseases of rice are of special concern. Rice is destroyed by 2 main pathogens, Fusarium oxysporum and Pyricularia oryzae the causative agents of root rot and blast in rice respectively. These pathogens result in low grain yield in Thailand and other Southeast Asian countries. Soil samples were taken from paddy fields in Northern Thailand and bacteria were isolated using the soil dilution plate method on Nutrient agar. Isolation yielded 216 bacterial isolates which were subsequently tested for their siderophore production and effectiveness in inhibiting mycelial growth in vitro of the rice pathogenic fungi; Alternaria sp., Fusarium oxysporum, Pyricularia oryzae and Sclerotium sp., the causal agent of leaf spot, root rot, blast and stem rot in rice. It was found that 23% of the bacteria isolated produced siderophore on solid plating medium and liquid medium, In dual culture technique, the siderophore producing rhizobacteria showed a strong antagonistic effect against the Alternaria (35.4%), Fusarium oxysporum (37.5%), Pyricularia oryzae (31.2%) and Sclerotium sp. (10.4%) strains tested. Streptomyces sp. strain A 130 and Pseudomonas sp. strain MW 2.6 in particular showed a significant higher antagonistic effect against Alternaria sp. while Ochrobactrum anthropi D 5.2 exhibited a good antagonistic effect against F. oxysporum. Bacillus firmus D 4.1 inhibited P. oryzae and Kocuria rhizophila 4(2.1.1) strongly inhibited Sclerotium sp. P. aureofaciens AR 1 was the best siderophore producer overall and secreted hydroxamate type siderophore. This strain exhibits an in vitro antagonistic effect against Alternaria sp., F. oxysporum and P. oryzae. Siderophore production in this isolate was maximal after 15 days and at an optimal temperature of 30°C, yielding 99.96 ± 0.46 μg ml-1 of siderophore. The most effective isolates were identified by biochemical tests and molecular techniques as members of the Genus Bacillus, Pseudomonas and Kocuria including B. firmus D 4.1, P. aureofaciens AR1 and Kocuria rhizophila 4(2.1.1). The study demonstrated antagonistic activity towards the target pathogens discussed and are thus potential agents for biocontrol of soil borne diseases of rice in Thailand and other countries. © Springer Science+Business Media B.V. 2009.